2000
DOI: 10.1038/35046592
|View full text |Cite
|
Sign up to set email alerts
|

Rough Deal and Zw10 are required for the metaphase checkpoint in Drosophila

Abstract: The metaphase-anaphase transition during mitosis is carefully regulated in order to assure high-fidelity transmission of genetic information to the daughter cells. A surveillance mechanism known as the metaphase checkpoint (or spindle-assembly checkpoint) monitors the attachment of kinetochores to the spindle microtubules, and inhibits anaphase onset until all chromosomes have achieved a proper bipolar orientation on the spindle. Defects in this checkpoint lead to premature anaphase onset, and consequently to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 29 publications
12
93
1
2
Order By: Relevance
“…It remains unclear whether the SAC component, Mps1p, also plays a role in centrosome duplication in higher eukaryotes [Fischer et al, 2004;Fisk et al, 2003;Liu et al, 2003;Stucke et al, 2004;Stucke et al, 2002] as it does in budding [Winey et al, 1991] but not in fission yeast [He et al, 1998]. The mammalian Ndc80p complex [McCleland et al, 2003], the ROD and ZW10 kinetochore proteins [Basto et al, 2000;Chan et al, 2000], the outer kinetochore protein Zwint-1 [Obuse et al, 2004;Wang et al, 2004a], and the kinetochore-associated NEK2A protein [Lou et al, 2004] are also required for the spindle checkpoint, indicating that the kinetochore's role in SAC signaling is evolutionarily conserved, although no ROD, ZW10, or Zwint-1 homologues have been identified in yeast. The mammalian survivin/Aurora B complex regulates BubR1p and Mad2p localization to kinetochores [Lens et al, 2003] and, like the budding yeast Ipl1p/Aurora, is required for SAC function when insufficient tension is applied across sister kinetochores [Carvalho et al, 2003;Hauf et al, 2003;Lens et al, 2003].…”
Section: Higher Eukaryotesmentioning
confidence: 99%
“…It remains unclear whether the SAC component, Mps1p, also plays a role in centrosome duplication in higher eukaryotes [Fischer et al, 2004;Fisk et al, 2003;Liu et al, 2003;Stucke et al, 2004;Stucke et al, 2002] as it does in budding [Winey et al, 1991] but not in fission yeast [He et al, 1998]. The mammalian Ndc80p complex [McCleland et al, 2003], the ROD and ZW10 kinetochore proteins [Basto et al, 2000;Chan et al, 2000], the outer kinetochore protein Zwint-1 [Obuse et al, 2004;Wang et al, 2004a], and the kinetochore-associated NEK2A protein [Lou et al, 2004] are also required for the spindle checkpoint, indicating that the kinetochore's role in SAC signaling is evolutionarily conserved, although no ROD, ZW10, or Zwint-1 homologues have been identified in yeast. The mammalian survivin/Aurora B complex regulates BubR1p and Mad2p localization to kinetochores [Lens et al, 2003] and, like the budding yeast Ipl1p/Aurora, is required for SAC function when insufficient tension is applied across sister kinetochores [Carvalho et al, 2003;Hauf et al, 2003;Lens et al, 2003].…”
Section: Higher Eukaryotesmentioning
confidence: 99%
“…Cytoplasmic dynein at kinetochores also does not appear essential for Mad2 binding to unattached kinetochores because we found Mad2 highly concentrated on kinetochores in prophase nuclei that show no staining for cytoplasmic dynein. In addition, depletion of zw10, rod, or dynein/dynactin also does not prevent Mad1, Mad2, or BubR1 from binding unattached prometaphase kinetochores (Chan et al, 2000), but zw10 and rod, proteins that target cytoplasmic dynein to kinetochores, do appear required for maintenance of checkpoint activity (Chan et al, 2000;Basto et al, 2000). Howell et al (2000) has shown that Mad2 binding sites are transported poleward from unattached kinetochores to the poles.…”
Section: Future Considerationsmentioning
confidence: 99%
“…In another study, Savoian and colleagues used zw10 and rod Drosophila mutant spermatocytes to specifically perturb dynein localization at kinetochores [99,100] and showed that anaphase chromosome motion to the poles was severely affected in those mutants. However, some potential caveats with this experimental approach are related with the fact that zw10/rod are also required to recruit the SAC protein Mad2 to unattached kinetochores, thereby compromising SAC function [101][102][103]. Kinetochore dynein is also involved in the initial MT capture at the entry of mitosis, which could indirectly compromise chromosome motility if anaphase is triggered with normal kinetics [100].…”
Section: Kinetochore Dyneinmentioning
confidence: 99%